Direct Oxidation of Csp3−H bonds using in Situ Generated Trifluoromethylated Dioxirane in Flow. Issue 5 (14th December 2018) - Lesieur, Mathieu; Battilocchio, Claudio; Labes, Ricardo; Jacq, Jérôme; Genicot, Christophe; Ley, Steven V.; Pasau, Patrick
Abstract: A fast, scalable, and safer Csp 3 −H oxidation of activated and un‐activated aliphatic chains can be enabled by methyl(trifluoromethyl)dioxirane (TFDO). The continuous flow platform allows the in situ generation of TFDO gas and its rapid reactivity toward tertiary and benzylic Csp 3 −H bonds. The process exhibits a broad scope and good functional group compatibility (28 examples, 8–99 %). The scalability of this methodology is demonstrated on 2.5 g scale oxidation of adamantane. Abstract : Faster, safer, scalable : A continuous flow concept allowed the direct Csp 3 −H oxidation of activated and un‐activated aliphatic chains via in situ formation of methyl(trifluoromethyl)dioxirane (TFDO). The reported procedure demonstrated a broad scope and good functional‐group compatibility (28 examples, 8–99 %).